Políticas inclusivas: características e tendências das produções acadêmicas em programas de pós-graduação em educação do Nordeste (2010-2018) - Andrade, Josiane Santiago dos Santos (2021)
This research aims to study the academic production focused on Inclusive Educational Policies, in the Graduate Programs in Education located in the Northeast region of Brazil, in the period 2010-2018, specifically theses and dissertations. The research problem was guided by the following central question: What are the characteristics and tendencies of academic productions (theses and dissertations) presented in graduate programs in education in the Northeast region that treat with inclusive policies in the period 2010-2018 and what contributions have they brought to the field regarding the method and epistemological bases? The general objective of the research was: to characterize and analyze theses and dissertations defended in the period 2010-2018 and that guided the inclusive policies, produced in graduate programs in education in the Northeast region, identifying the predominant theoretical-methodological tendencies and contributions to the field of study in inclusive policies. As for the theoretical and methodological orientations, this is a research inspired by critical theory, whose denomination was assumed by the Frankfurt School, which proclaims the articulation between social criticism and human emancipation, as a historical project. Inspired by the thought of Theodor W. Adorno, the research also gave way to other contemporary intellectuals, in particular Crochik (2007, 2011), Crochik et.al (2009, 2013). In the light of the reference, the notion of Inclusive Education has assumed from the beginning of the work, covering the double dimension with respect to diversity and to face the processes of inequality production in relation to minorities. This understanding is associated with the recognition that the achievements around inclusive education do not result from spontaneity, but organized actions and struggles emanating from discriminated social groups, in the context of historical movements of resistance to the different forms of segregation and social hierarchy that produce marginality and inequality. Combined with this, the research was guided by the simultaneous effort of characterization of productions, analysis and identification of possible signs of struggles within the field of education, faced with the diversity and conflict of approaches. Regarding methodological strategies, the research was oriented by the assumptions of the review studies, according to State of Art parameters, based on Vosgerau and Romanowski (2014). The corpus, constuting of theses and dissertations, revealed that productions focusing on Inclusive Education have prioritized the political and social dimensions that circumstantiate the thematic clippings. The choices in this direction point out concerns with the situations of the subjects of law in a relational way, including physical, intellectual, social and/or political aspects. The studies indicate a great convergence with the approaches that relate education and emancipation, although there is also a great diversity of epistemological contributions, such as: phenomenological, historical-social, historical-discursive approach and theory of inclusion/inclusion, intercultural, cultural studies of education, dialectical materialism and the theory of social representation, indicating that there is no hegemony of a specific interpretation about inclusion.